Mapping of marine lobster research: A global outlook - Azra, Mohamad Nor; Jye, Mok Wen; Van Doan, Hien; Zekker, Ivar; Abdullah, Muhammad Fuad; Abd Latif, Zulkiflee; Noor, Mohd Iqbal Mohd (Frontiers in Marine Science, 2022)
This study examined research and development of the commercially important marine lobster, in terms of descriptive metadata and scientometric analysis. We consider a collection of over 9,578 related articles to assess literature patterns and research development trends related to marine lobsters as a topic. Web of Science Core Collection was used to identify, collate, and generate publication trends, a list prominent authors and affiliations involved, countries that actively participated, and the co-citation analysis of the references as well as impactful articles and keywords. There were 149 different countries or states that had relevant publications on lobster research. We found an increase in the number of publications over time, with the USA having the most number of publications, followed by Australia and Canada. A total of 17,782 authors were involved in the field of lobster studies. Canadian researchers had the highest citation count for marine lobster research. Surprisingly, the most impactful keyword was crayfish, followed by neuron and amino acid sequence. Our study identifies the multidisciplinary nature in marine lobster research, which includes fields such as neuroscience and developmental genetics. We find that lobster scientific publications increasingly centre on the broader coverage areas of science such as taxonomy and basic biology.